Improving Home Sanitation and Personal Hygiene as a Stunting Prevention Effort in Liliba Village, Oebobo District, Kupang City - Albina Bare Telan; Agustina; Edwin Mesach M Mauguru; Olga Dukabain (Unram Journal of Community Service, 2026)
This Community Service (PKM) activity aims to improve home environmental sanitation and personal hygiene as an effort to prevent stunting in Liliba Village, Kupang City, an area with a relatively high stunting rate. The activity was carried out at the Melati 11 Integrated Health Post (Posyandu) and targeted mothers with stunted toddlers and Posyandu cadres. The intervention was carried out through health education on home sanitation and personal hygiene, knowledge assessments using pre- and post-tests, and the repair of one family toilet unit that previously did not meet environmental health requirements. The results of the activity showed an average increase in knowledge of participating mothers by 7–8% after the education, accompanied by an increased understanding of clean and healthy living practices (PHBS). The enthusiasm of the participants in the discussion indicated a good receptivity to the material. In addition, the toilet repair has resulted in a sanitation facility that meets healthy toilet standards and is expected to serve as a model for other families. Overall, this program is effective in increasing the knowledge, awareness, and quality of sanitation of families at risk of stunting. This activity also supports the achievement of the STBM pillars, especially Stop Open Defecation (BABS), and provides a real and sustainable impact on the community.